Entre memórias e histórias de uma pedagoga ribeirinha - BAÍA, Madalena Vilhena (2024)
In order to describe my professional career in a critical and reflexive way, the present memorial, among other things, enabled me to describe the facts of my daily life and its vast breadth, in relation to the relationships I experienced the interpersonal. The agents who have made and are part of this human web are the students, professors, undergraduate professors, directors, employees, members of my family who, in a direct or indirect way, were decisive for the effective and affective performance of my teacher. The memories and stories present here are accompanied by reflection on the above facts. This was only possible through theorists such as Andrade (1999), Borba (2006), Cury (2003), Freire (2000), Moreira (2008) and Smole (2007) with each detailed fact. To all who share this reading, I wish to have in the interpretations and reflections present in this memorial the opportunity to cross information and knowledge with our own personal practices, in order to add experiences in our relationships in the educational context.